Insights into the diagnosis, vaccines, and control of Taenia solium, a zoonotic, neglected parasite - Hossain, Md. Shahadat; Shabir, Shafqat; Toye, Philip; Thomas, Lian F.; Falcone, Franco H.; Justus Liebig University Giessen (My University, 2023)
Taenia solium taeniasis/cysticercosis (TSTC) is a foodborne, zoonotic neglected tropical disease affecting predominately low- and middle-income countries. Humans are definitive hosts for T. solium, whereas pigs act as intermediate hosts. Taeniasis, i.e. intestinal infection with adult T. solium in the human host, occurs through ingestion of undercooked pork infected with the larval stage (porcine cysticercosis, PCC). Human cysticercosis occurs after humans ingest T. solium eggs, acting as accidental intermediate hosts. Migration of cysticerci to the human brain results in neurocysticercosis (NCC), manifesting in a variety of clinical symptoms, most notably epilepsy. NCC is the leading cause of acquired epilepsy cases in endemic areas. PCC results in reduced pork value because of condemnation or the risk of condemnation of the meat. Available serological diagnostic tests for porcine and human cysticercosis are characterized by low sensitivity and are not cost-effective. An effective vaccine for T. solium cysticercosis in pigs has been developed, although it is not yet commercially available in all endemic countries, and still no vaccine is available for use in humans. This primer highlights the recent development in the field of diagnostic tests and vaccine production and explores possible strategies for future control and eradication of T. solium. In the absence of highly specific diagnostic tests and human vaccines, treatment of infected pigs and tapeworm carriers and prevention of disease transmission remain the principal means to interrupt the zoonotic cycle of T. solium in endemic countries.
Keywords: ddc:630